USAHA DAUR ULANG LIMBAH PLASTIK DI KECAMATAN TENAYAN RAYA PEKANBARU - Meiliza, Yolanda; Erita, Yeni; Iswandi U, Iswandi U (Pendidikan Geografi, 2013)
This Research aim to to get information and data about Effort Recycle Waste Plastic In District Of Great Tenayan of Pekanbaru. got Data use the following indicator ; (1) Processing of plastic waste, (2) Area product marketing of recycle, (3) Amount of managed plastic waste, (4) Earnings of labour, (5) yielded Type product.Research type the used is descriptive, meaning research method or resolving procedure investigated depicting and defining objective situation of research at the time of now pursuant to visible facts or as it is, Arikunto ( 2006). Research Subjek is entrepreneur recycle plastic waste as especial informan and labour as additional informan.Technique data collecting pass/through observation, filling photograph and enquette. Technique analyse data which is used in research is by data discount, displayed by data, data interpretation and decision making.Result of research show processing of plastic waste done/conducted in 5 phase that is election, wash, draining, stitching and clip or matting. This matter is done/conducted product to which in recycle with quality. Marketing done/conducted directly sell goods result of recycle to society, advertisement of diinternet, and exhibition. Target of marketing area among others Pekanbaru and have to Java. Amount of waste the managed is 300 singk / month;moon. Amount of the managed waste yielded from household plastic waste. Earnings of month;moon labour at effort mean recycle of Rp. 500.000 / months.